2018
DOI: 10.1186/s12909-018-1290-3
|View full text |Cite
|
Sign up to set email alerts
|

Independent investigator incubator (I3): a comprehensive mentorship program to jumpstart productive research careers for junior faculty

Abstract: BackgroundIn the highly competitive environment of academic medicine, junior faculty investigators face high attrition rates due to challenges in finding effective mentorship, securing grant funding, and obtaining resources to support their career development and research productivity. The purpose of this study was to describe the centralized, cost-sharing design of the Independent Investigator Incubator (I3) program as a novel approach to junior faculty mentoring and to evaluate quantitative outcomes for prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 22 publications
(23 reference statements)
1
45
0
Order By: Relevance
“…The importance of mentorship has been demonstrated in several recent studies and has been linked to faculty satisfaction, vitality, climate, and productivity. [15][16][17] Mentorship is widely regarded as a key component in retention of faculty at academic medical centers. 18,19 Despite the known value of mentoring, StandPoint Surveys reports that only 30% of faculty are engaged in formal mentorship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of mentorship has been demonstrated in several recent studies and has been linked to faculty satisfaction, vitality, climate, and productivity. [15][16][17] Mentorship is widely regarded as a key component in retention of faculty at academic medical centers. 18,19 Despite the known value of mentoring, StandPoint Surveys reports that only 30% of faculty are engaged in formal mentorship.…”
Section: Discussionmentioning
confidence: 99%
“…Our data support prior studies demonstrating that junior faculty should receive formal mentorship from an early stage. [15][16][17][18][19] In addition, faculty should have opportunities for careerenhancing activities at their institution or as offered by their professional societies. A robust annual review process for each faculty is a good way to provide performance feedback, recognize achievements, and prepare career development priorities for the upcoming year.…”
Section: Most Pressing Concerns Of Faculty Expressing An Intent To Leavementioning
confidence: 99%
“…A pilot study at the Indiana University School of Medicine found that 80% of individuals who participated in a mentorship program successfully published a manuscript. This survey suggested that mentorship increases research productivity through increased opportunity, professional and personal development such as research proficiency, interpersonal skills, and career development skills [27].…”
Section: Solutionsmentioning
confidence: 99%
“…Mentorship can improve mentee productivity, self-efficacy and career satisfaction [11][12][13][14] and be a personally fulfilling experience for mentors [15,16]. Wellstructured and inclusive mentoring programs are highly beneficial for health professionals, including training researchers across varied disciplines [12,[17][18][19][20][21][22][23][24]. Mentoring relationships that offer the greatest impact on success are likely to be influenced by individual attributes [25] and the social context within which the program is instituted [26].…”
Section: Introductionmentioning
confidence: 99%